Dr. Stone. 6, Stone wars - Inagaki, Riichiro (Shonen Jump manga., 2019)
"One fateful day, all of humanity turned to stone. Many millennia later, Taiju frees himself from the petrification and finds himself surrounded by statues. The situation looks grim--until he runs into his science-loving friend Senku! Together they plan to restart civilization with the power of science!... Senku's father, the astronaut Byakuya, returned to Earth shortly after humanity turned to stone. What did he leave behind for his son to discover thousands of years later? In the meantime, Senku and the villagers have to contend with attackers from the Tsukasa Empire. The dire situation calls for drastic measures, so they start work on their strongest weapon yet."--Provided by publisher.